Development of elemental cost analysis (ECA) web-based application platform / Shariffah Zatil Hidayah Syed Jamaludin ... [et al.] - Syed Jamaludin, Shariffah Zatil Hidayah; Kipli, Kumalasari; Nizam Akhbar, Anis Rosniza; Ibrahim, Irma Hanie; C. Alih, Suzana; Mat Jusoh, Abdul Rahman (College of Built Environment, 2023)
The cost estimation at the inception stage is important to forecast the actual budget of the project.